2016
DOI: 10.7860/jcdr/2016/20398.8394
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Radiation Hazards, Radiation Protection Practices and Clinical Profile of Health Workers in a Teaching Hospital in Northern Nigeria

Abstract: This study demonstrated poor radiation protection practices despite good knowledge of radiation hazards among the participants, but radiation exposure and prevalence of abnormal clinical conditions were found to be low. Periodic in-service training and monitoring on radiation safety was suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
4
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 16 publications
8
21
4
6
Order By: Relevance
“…These results are consistent with the present study in the lack of practice; despite the fact that enough protective tools were available for them, . Awosan et al (2016) in a crosssectional study among radiology, radiotherapy and dentistry staff, found that there was good awareness of radiation hazards among the participants but, poor radiation protection practice was noted, which is similar to the present study.…”
Section: El-feky Et Al (2017) Reportedsupporting
confidence: 88%
“…These results are consistent with the present study in the lack of practice; despite the fact that enough protective tools were available for them, . Awosan et al (2016) in a crosssectional study among radiology, radiotherapy and dentistry staff, found that there was good awareness of radiation hazards among the participants but, poor radiation protection practice was noted, which is similar to the present study.…”
Section: El-feky Et Al (2017) Reportedsupporting
confidence: 88%
“…Although professional workers were aware of the physical risk associated with working in a facility without adequate safety systems, the majority of them continued to work in the risk scenarios. This finding is in line with the reported poor radiological protection in another study [22]. The working in a radiotherapy facility without / malfunctioned radiation detection systems such as radiation zone monitor, survey meters, and PMD, etc.…”
Section: Discussionsupporting
confidence: 88%
“…This result was contrary to the results obtained from the study of (26)(27)(28). based on our study and con rmation of studies Briggs-kamara et al and Ria et al, it was found that patients' awareness was de cient (18,19,26,29,30), It should be noted that in our study, most radiation students and staff thought they were well aware and did not need to undergo training. However, in studies Masoumi et al and Rostamzadeh et al, it was found that training reduces radiation risks and increases radiation awareness (27,31).…”
Section: Discussionsupporting
confidence: 84%